Jan Paweł II wobec badaczy antyku chrześcijańskiego - Wiesław Dawidowski (Vox Patrum, 2007)
Anyone undertaking a task to describe an attitude of John Paul II towards scholars of antiquity faces two problems: the innumerable mass of people he met throughout his life carrier and his personal scholar path which was not primarily patristic. He went from John of the Cross, Thomas Aquinas, Max Scheller towards contemporary phenomenology. Yet, „the Polish Pope” was gradually getting more and more interested in patristic studies. This article is a short study in Wojtyla’s understanding of the work, the method and the tasks of contemporary patrologists. In an allocution to the representatives of the Institute Sources Chretiennes, John Paul II declared that the development of patristic studies stayed in the bottom of his heart, for a credible formation of Christian intelligentsia, must always appeal to the fathers of our faith. Consequently, he considered patristic scholars’ work, as a bridge between life giving sources of theological knowledge i.e. Holy Scripture, Tradition of the Fathers and still unknown bank of the third millennium. Holy Father appraised and highly estimated historical-critical method applied in patristic studies. To understand the meaning of dogmas, the relation between the Holy Scriptures, Tradition and Magisterium, the Church cannot withhold from studies in antiquity. Humility, patience and perseverance are the most distinguished Christian virtues that should characterize scholars of antiquity. To a certain degree, Pope’s esteem towards patristic scholars, was noticeably accentuated by numerous nominations of the most distinguished patristic scholars to the honor of episcopate. The main message that John Paul II implicitly directed towards contemporary scholars of antiquity seemed to concentrate on pastoral dimension and reduced to a one phrase. If there is anything that, in the deformed and chaotic world of contemporary theology and philosophy, could restitute harmony and balance, it is the teaching of the Fathers of the Church.